Trojan Odyssey - Cussler, Clive, author 191823 (London : Penguin Books, 2004)
A daring rescue sends Dirk Pitt on an adventure that will determine the future of the planet ...When a hurricane unexpectedly blows up off the coast of Nicaragua, a giant floating hotel lies in its path. With no escape for the helpless passengers and crew, it's left to Dirk Pitt and NUMA to launch a rescue and save the day. But in the storm's wake, Pitt and his team discover clues that point to an ancient mystery with shocking implications for today. As Pitt investigates further, he uncovers a plot by a mysterious billionaire called Specter to dramatically alter the Earth's climate, leaving him in control of the only solution. With foes attempting to stop him on every side, Pitt is in a race against time to prevent global catastrophe...